An adaptive force/position control scheme for robot manipulators - Chiaverini, Stefano; Siciliano, Bruno; Villani, Luigi (Zielona Góra: Uniwersytet Zielonogórski)
An adaptive control scheme is proposed for controlling both the force and position for a robot manipulator in contact with a compliant surface. The controller is developed in the framework of parallel control of inverse-dynamics type. Adaptation to unknown stiffness is achieved by resorting to a suitable estimate update law driven by the force error.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka